Thromboembolism in adults with primary immune thrombocytopenia: a systematic literature review and meta‐analysis. (20th June 2016) - Doobaree, Indraraj Umesh; Nandigam, Raghava; Bennett, Dimitri; Newland, Adrian; Provan, Drew
Abstract: Adults with primary immune thrombocytopenia (ITP) may be susceptible to thromboembolism (TE). The objective of this systematic review was to evaluate studies that reported the prevalence and risk of developing TE in the ITP population from ITP diagnosis and splenectomy. We searched several bibliographic databases and included 29 studies. Using meta‐analytical techniques, the pooled prevalence of TE before ITP diagnosis was 7.84% (arterial 6.25%; venous 1.95%). The pooled 'annualised' cumulative incidence (without prior TE) and cumulative risk (irrespective of prior TE) were 1.29%/yr and 3.00%/yr, respectively. Splenectomised patients had pooled cumulative risk of arterial TE (ATE) and venous TE (VTE) of 0.19%/yr and 1.10%/yr, respectively. In cohorts, regardless of a history of TE, the pooled relative risk (RR) of any TE was 1.60 (1.34, 1.86) for ITP vs. ITP‐free individuals [arterial: 1.52 (1.25, 1.80); venous: 1.70 (0.96, 2.43)]. Splenectomised patients were at higher risk of venous events, pooled RR 2.39 (1.61, 3.17). To conclude, we found an increased risk of TE (mainly ATE) among ITP individuals and a higher risk of VTEs after splenectomy. How intrinsic (ITP pathophysiology, age, gender) and extrinsic factors (treatment) contribute to this risk could not be investigated here but is a task for future studies.